Manajemen Pendidikan Karakter dalam Membentuk Siswa Berakhlakul Karimah di Madrasah Aliyah Zainul Hasan 2 Mojolegi - Sholehah, Riskawati; Izzah, Ismatul; Yunita, Arifia Retna (CV. Creative Tugu Pena, 2024)
This study aims to investigate the implementation of character education management in shaping students with good character at Madrasah Aliyah Zainul Hasan 2 Mojolegi. Character education management is directed at developing students' moral values, ethics, and spirituality to build good character and noble character. A qualitative approach was used in this study with data collection techniques in the form of observation, interviews and documentation studies. Respondents consisted of teachers, school staff, and students of Madrasah Aliyah Zainul Hasan 2 Mojolegi. Data analysis was conducted through a process of data reduction, display, and verification. The research findings show that character education management in the madrasah involves extracurricular activities, academic coaching and strengthening religious values in the curriculum. In addition, collaboration between teachers, parents and the community is the main key in creating an educational environment that supports student character building. The results of this study are expected to provide input for education stakeholders in improving the effectiveness of character education management at Madrasah Aliyah Zainul Hasan 2 Mojolegi as well as in other educational institutions. Keywords: Achievement of Basic Competencies, Larning Fiqh, Basic Competencies Knowledge and Skills